Improving Tuna Chili Product Quality at KWT Larasati through Food Safety Education - Riska Ayu Febrianti; Ani Rosa Putri Ayu Mujayanah; Akbar Pandu Segara; Erlia Narulita; Intan Ria Neliana; Moh Dliyauddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Food safety is a crucial aspect of small-scale processed food production, particularly for fish-based products such as tuna chili sauce, which are highly susceptible to contamination and quality deterioration. This community service program aimed to improve the knowledge and awareness of members of Kelompok Wanita Tani (KWT) Larasati regarding the application of food safety principles in tuna chili sauce production. The program was conducted in 2025 at the KWT Larasati production site using an educational and participatory approach, including food safety counseling, interactive discussions, and on-site mentoring and observation. The effectiveness of the program was evaluated using pre-test and post-test instruments to assess changes in participants’ knowledge levels, as well as an observation checklist based on Good Manufacturing Practices for small and micro food enterprises (Cara Produksi Pangan Olahan yang Baik/CPPOB) to evaluate hygiene and sanitation practices. Data were analyzed using descriptive quantitative methods by comparing mean pre-test and post-test scores, and qualitative descriptive analysis of field observations. The results showed a substantial increase in the average food safety knowledge score from 48 to 85 after the educational intervention. Initial improvements were also observed in several food safety practices, including workers’ personal hygiene, equipment cleanliness, production flow arrangement to reduce the risk of cross-contamination, and the completeness of basic product labeling information. Although the implementation of food safety principles has not yet been fully consistent, this program proved effective as an initial step in enhancing food safety awareness and encouraging improvements in production practices. This community service program is expected to serve as a foundation for strengthening the sustainable implementation of CPPOB to improve the quality, safety, and competitiveness of tuna chili products in small-scale food enterprises.